97 Paralysis From an Ear Infection: A Severe Case of Otitis Externa Leading to Acute Complete Cervical Cord Syndrome. (28th February 2022) - Collins, R.; Lafford, G.
Abstract: We report a case of a generally fit and well 54-year-old gentleman who presented with a two-day history of worsening left sided ottorhea, headache, neck stiffness, vomiting and pyrexia on the background of a seven-week history of OE. His condition progressed dramatically as he developed symptoms consistent with acute complete cervical cord syndrome with radiological evidence of skull base osteomyelitis, parapharyngeal, retropharyngeal and paravertebral abscesses and sigmoid sinus thrombus. Ultimately, he made a significant, although not complete, recovery. This case is unique in demonstrating how OE can develop into a potentially life-threatening condition. It emphasises the importance of early diagnosis and treatment of OE, the recognition of 'red flag' symptoms and highlights the importance of a multi-disciplinary team (MDT) approach when managing complex complications of OE.